New Discoveries in Embryology - Wu, Bin; Wu, Bin (IntechOpen, 2015)
Animal individual life begins as combination of sperm and oocyte, which results in the embryogenesis from ovum fertilization to fetal stage. Embryology has become one central discipline for many modern biotechnologies. Although this subject has been studied for more than a century, new discoveries appear continuously. This book contains some new discoveries and updates some theories and technologies in animal and human embryology. Major content include new findings in gamete biology, new theories and discoveries in embryo implantation by three-dimensional imaging technology and new concept and actual application of embryology. Thus, this book will greatly update knowledge in embryology field and provide some basic theories and technologies for animal scientists and breeders as well as embryologists and anthropologists.
English
Keywords: Physiology; Embryology